What Do You Do With Hands Like These? Close Reading Facilitates Exploration and Text Creation - Lindsey Moses (CLELEjournal, 2013)
This article shares instructional ideas to enhance language and literacy experiences involving the reading and writing processes of young bilinguals (Spanish and English) in Colorado, USA when engaging with informational texts. Informational texts provide language scaffolds for young bilinguals because they build on their background knowledge about the world around them. Drawing on their recognition of real-world concepts found in informational texts, teaching ideas that enrich both academic and social vocabulary are shared. These teaching ideas suggest moving beyond the read aloud and individual reading of informational texts; they suggest instead teaching young learners to 'read like writers' and utilize Jenkins and Page's What Do You Do With a Tail Like This? (2003) as a mentor text. This article includes relevant research, teaching ideas and classroom examples for scaffolding a close reading, ultimately resulting in intercultural explorations as the children share their writing about their home contexts.